MATH SOLVE

4 months ago

Q:
# If f(x) = 5x - 2 and g(x) = 2x + 1, find (f + g)(x)

Accepted Solution

A:

Answer:(f + g)(x) = 7x - 1Step-by-step explanation:Given : f(x) = 5x – 2 and g(x) = 2x + 1We have to find (f + g)(x)Consider (f + g)(x) = f(x) + g(x)Also, given f(x) = 5x – 2 and g(x) = 2x + 1Substitute, we have, f(x) + g(x) = 5x - 2 + 2x + 1 Like Terms are terms having same variable with same degree.Simplify by adding like terms, we have, f(x) + g(x) = 5x + 2x - 2 + 1 f(x) + g(x) = 7x - 1Thus, (f + g)(x) = 7x - 1